CONTROL ANALYSIS OF COTTON AND COTTON PRODUCTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article recommends a coordinated technology (regulation) for each ginnery to create its own technology (regulations) depending on its condition and available equipment. Also, information was also provided on the functions of Department of Technical Control (DTC) in cotton plants.